The relationship between internationalisation and firm performance in South Africa: the moderating role of slack resources - Sebola, Peter (College of Accounting, 2026)
Firm internationalisation has emerged as a crucial growth strategy in an increasingly globalised world. As firms strive to expand their operations beyond their home countries, they face several opportunities as well as challenges. While the effects of internationalisation on firm performance have been extensively studied, conclusive findings remain elusive due to a variety of factors. In particular, its specific implication for South African firms remains under-studied. Furthermore, there is a significant gap in the literature regarding how slack resources moderate this relationship. This study aims to analyse the relationship between the degree of internationalisation and firm performance among South African firms. It also examines how absorbed and unabsorbed slack resources influence this relationship. Employing a regression model, this study uses panel data from internationalised South African firms listed on the Johannesburg Stock Exchange between 2010 and 2019, providing a rich long-term dataset for analysis. The results indicate an insignificant relationship between the degree of internationalisation and firm performance, suggesting that increased internationalisation does not impact financial performance. The results also indicate that increasing absorbed and unabsorbed slack resources have an insignificant moderating effect on this relationship. This study contributes to the existing body of knowledge by providing insight into how firm internationalisation relates to performance, while considering the moderating effects of firm-specific factors. Additionally, it enhances the understanding of firm internationalisation in the emerging market context of South Africa. These findings offer practical implications for South African firms aiming to expand internationally, highlighting the importance of strategic resource allocation during internationalisation.